PENGARUH ROA, DIVIDEND YIELD DAN EPS TERHADAP FIRM SIZE PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BEI - Lisa Priscilia D; Frumeyza Chabella S; Lista Qotrun N (Nusantara Hasana Journal, 2023)
Seeing the changes in economic growth that shifted during the pandemic, people began to realize how important it is to collect and develop the assets they have, for unlimited needs or wants in the future. However, as a potential investor it is important to observe and analyze assets or companies that intend to be invested or invested. One way that potential investors can do is to measure how well the company operates in running its business, one of the tools that can be used is to analyze the company's financial statements. There are three ratios that can be used by potential investors in determining how well the company's operations are, namely, Return On Assets (ROA), Dividend Yield (DY) and Earning Per Share (EPS) etc. The method used in this study is the multiple linear regression method with hypothesis testing t-test and f-test, before using the multiple linear regression method, the classical assumption test is carried out first. The results of this study prove that the ROA variable has no significant effect on firm size, while the DY and EPS variables have a significant effect on firm size.